Impact of an enhanced recovery after surgery protocol on short-term outcomes in elderly patients undergoing pancreaticoduodenectomy. Issue 10 (October 2022) - Raza, Syed S.; Nutu, Oana A.; Powell-Brett, Sarah; Carvalheiro Boteon, Amanda; Hodson, James; Abradelo, Manuel; Dasari, Bobby; Isaac, John; Chatzizacharias, Nikolaos; Marudanayagam, Ravi; Mirza, Darius F.; Roberts, J. Keith; et al.
Abstract: Background: To determine whether the short-term benefits associated with an enhanced recovery after surgery programme (ERAS) following pancreaticoduodenectomy (PD) vary with age. Methods: 830 consecutive patients who underwent PD between January 2009 and March 2019 were divided according to age: elderly (≥75 years) vs. non-elderly patients (<75 years). Within each age group, cohort characteristics and outcomes were compared between patients treated pre- and post-ERAS (ERAS was systematically introduced in December 2012). Univariable and multivariable analysis were then performed, to assess whether ERAS was independently associated with length of hospital stay (LOS). Results: Of the entire cohort, 577 of 830 patients (69.5%) were managed according to an ERAS protocol, and 170 patients (20.5%) were aged ≥75 years old. Patients treated post-ERAS were significantly more comorbid than those pre-ERAS, with a mean Charlson Comorbidity Index of 4.6 vs. 4.1 (p < 0.001) and 6.0 vs. 5.7 (p = 0.039) for the non-elderly and elderly subgroups, respectively. There were significantly fewer medical complications in non-elderly patients treated post-ERAS compared to pre-ERAS (12.4% vs. 22.4%; p = 0.002), but not in elderly patients (23.6% vs. 14.0%; p = 0.203). On multivariable analysis, ERAS was independently associated with reduced LOS in both elderly (14.8% reduction, 95% CI: 0.7–27.0%, p = 0.041) and non-elderly patients (15.6% reduction, 95% CI: 9.2–21.6%, p < 0.001), with the effect size being similar in each group. Conclusion: ERAS protocols can be safely applied to patients undergoing pancreaticoduodenectomy irrespective of age. Implementation of an ERAS protocol was associated with a significant reduction in postoperative LOS in both elderly and non-elderly patients, despite higher comorbidity in the post-ERAS period.